The Mazzel Ritual - Siegel, Dina. author. aut Link
XXIII, 219 p.
Keywords: The academic study of diamonds is as multi-faceted as the precious stones themselves. Mineralogists and geographers have written about them, as have historians and economists and students of art and fashion. They each shine their light on a different aspect of this source of luminous radiance. But who would venture to describe the entire complicated worldwide system starting in the diamond mines and ending with the consumers of Western metropolises? In The Mazzel Ritual: Culture, Customs and Crime in the Diamond Trade, Russian-Israeli cultural anthropologist and criminologist Dina Siegel follows the route of a diamond from the mines of Africa to the shops of Europe and the United States, as it passes through countless hands and places and is smuggled, stolen, cut, polished, sold, exchanged and, finally, worn as jewelry. In the course of this long and exciting journey, a wide range of people face all sorts of risks and criminality, as well as various moral and ethical judgments. Siegel describes the range of ethnic groups that are active in the diamond trade and the culture and customs that are specific to this business. She analyses the dangers and threats to the industry and aims to uncover the strategies and tactics to deal with them. Finally, this story of risk, trust and crime examines the vulnerability of diamond production and distribution to illicit and criminal activities. This book is about the diamond business itself as well as about those involved in it. It tells the story of people who simply cannot stay away from this expensive and alluring commodity.